Different sulfonylureas induce the apoptosis of proximal tubular epithelial cell differently via closing KATP channel - Rui Zhang; Xiaojun Zhou; Xue Shen; Tianyue Xie; Chunmei Xu; Zhiwei Zou; Jianjun Dong; Lin Liao (BMC, 2018)
Abstract Background Sulfonylureas (SUs) are widely prescribed for the treatment of type 2 diabetes (T2DM). Sulfonylurea receptors (SURs) are their main functional receptors. These receptors are also found in kidney, especially the tubular cells. However, the effects of SUs on renal proximal tubular epithelial cells (PTECs) were unclear. Methods Three commonly used SUs were included in this study to investigate if different SUs have different effects on the apoptosis of PTECs. HK-2 cells were exposed to SUs for 24 h prior to exposure to 30 mM glucose, the apoptosis rate was evaluated by Annexin/PI flow cytometry. Bcl-2, Bax and the ratio of LC3II to LC3I were also studied by western blot in vitro. Diazoxide was used to evaluate the role of KATP channel in SUs-induced apoptosis of PTECs. A Student's t-test was used to assess significance for data within two groups. Results Treatment with glibenclamide aggravated the apoptosis of HK-2 cells in high-glucose, as indicated by a significant decrease in the expression of Bcl-2 and increase in Bax. Additionally, the decreased LC3II/LC3I reflects that the autophagy was inhibited by glibenclamide. Similar but less pronounced change was found in glimepiride group, however, nearly opposite effects were found in gliclazide group. Further, the effects of glibenclamide on apoptosis promotion and the decreased LC3II/LC3I were ameliorated obviously by treatment with 100uM diazoxide. The potential protection effect of gliclazide was also inhibited after opening the KATP channel. Conclusion Our results suggest that, the effects of glibenclamide and glimepiride on PTECs apoptosis, especially the former, were achieved in part by closing the KATP channel. In contrast to glibenclamide and glimepiride, therapeutic concentrations of gliclazide showed an inhibitory effect on apoptosis of PTECs, which may have a benefit in the preservation of functional PTECs mass.